THE VALUE OF CHARACTER EDUCATION IN MEKONGGA FOLKLORE IN KOLAKA, SOUTHEAST SULAWESI - La Ode Topo Jers; Rahmat Sewa Suraya; Alias Alias; Ashmarita Ashmarita; La Ode Muhammad Ruspan Takasi; Rudy Kurniawan (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
The socio-cultural situation of the Mekongga people in Kolaka is known to have a lot of oral literature, one of them called folklore. The importance of strengthening character education in Mekongga community is carried out through the use of local folklore as a basis for inculcating moral values. Scientific studies on the phenomenon of moral values in folklore are still scarcely carried out, especially in Mekongga folklore. To that end, this study aims to analyze and describe the moral values of the Mekongga folklore in Kolaka Regency. This study uses a qualitative approach with the technique of determining the informant is a purposive sampling technique. Data collection methods in this study include the methods of observation, interviews, and documentation. Meanwhile, the data that has been collected is analyzed through qualitative descriptive techniques. The results of this study indicate that there are various forms of character education values contained in the mekongga folklore starting from the value of responsibility, trustworthiness, honesty, patience, love, courage, caring, humility, wisdom, courtesy, and trust. The values of character education are used in forming a wise and humane person, moreover, as an effort to realize harmonization, harmony, and unity in social life in Kolaka, Southeast Sulawesi which is multicultural.